2016
DOI: 10.1097/md.0000000000004290
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left and right ventricular myocardial function after lung resection using speckle tracking echocardiography

Abstract: The impact of major lung resections on myocardial function has not been well-investigated. We aimed to identify this impact through the use of speckle tracking echocardiography (STE) to evaluate the right and left ventricular myocardial function in patients who underwent lung resections.Thirty patients who had lung resections were recruited for this study. Ten patients who underwent pneumonectomies were matched by age and sex, with 20 patients who underwent lobectomies. STE was performed on both right and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…These results were in agreement with Wang et al [ 15 ] who studied 30 patients underwent lung resections, and speckle tracking echocardiography was performed. EF significantly decreased after resection but stayed within the normal range >55% with significant increase in HR.…”
Section: Discussionsupporting
confidence: 92%
“…These results were in agreement with Wang et al [ 15 ] who studied 30 patients underwent lung resections, and speckle tracking echocardiography was performed. EF significantly decreased after resection but stayed within the normal range >55% with significant increase in HR.…”
Section: Discussionsupporting
confidence: 92%
“…16 There are reports evaluating the effects of lung resection on RV by using RV strain. 17 We demonstrated that in congruence with other parameters, RV strain deteriorated on POD 2 and later improved over one month. However, LV strain did not change significantly postoperatively.…”
Section: Discussionmentioning
confidence: 83%
“…It has been demonstrated previously that more extensive lung resection is associated with postoperative RV dysfunction. 7,8 This has been hypothesized to result from larger increases in RV afterload associated with resection of larger proportions of the pulmonary vascular bed, negatively affecting RV function. It is plausible that the association between MINS and the extent of resection seen by Gonz alez-Tallada et al represents the potential for larger increases in RV afterload associated with pneumonectomy compared with smaller resections.…”
Section: Don't Forget the Right Ventriclementioning
confidence: 99%